Memes, masculinity and mancession: Love/Hate's online metatexts. Issue 2 (3rd April 2017) - Ging, Debbie
Abstract: Since it first aired in 2010 on Radió Teilifís Éireann, Ireland's national public service broadcaster, Irish crime drama series Love/Hate has enjoyed record audience ratings. However, while serious TV critics and the show's producers have praised it as a complex and incisive commentary on crime in Ireland, the more participatory online cultures of the Journal.ie, Twitter and Facebook have constructed a distinctly less highbrow set of discourses around the show. This analysis of the Journal.ie 's Daily Edge recaps demonstrates how participatory Laddish humour and what Jean Burgess refers to as the "vernacular creativity" of memes have functioned to prioritise a cohesive set of engagements with Love/Hate that are underpinned by fantasies about the recuperation of male power. Moreover, by creating a sense of "in-groupness" around the series, the Daily Edge and its tertiary texts have produced a heavily gendered sense of consensus about who "we" in post-Celtic Tiger Ireland are.